Is Russia Still Driving Regional Economic Growth? - Pani, Marco; Jafarov, Etibar; Shiells, Clinton (Washington, D.C. : International Monetary Fund, 2005)
This paper investigates whether the linkages between economic growth in Russia and growth in other countries in the region have weakened over time, particularly following the 1998 Russian crisis. It specifies an econometric model that includes standard growth determinants as well as Russian economic growth, and which allows for the effects of Russian growth to vary over time. The paper finds that Russian growth was indeed a significant determinant of regional economic growth prior to the Russian crisis, but that this link weakened significantly thereafter.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet